2001
DOI: 10.1097/00003446-200110000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Should Children Who Use Cochlear Implants Wear Hearing Aids in the Opposite Ear?

Abstract: Hearing aids for children who also use cochlear implants can be selected using the NAL-RP prescription. Adjustment of hearing aid gain to match loudness in the implanted ear can facilitate integration of signals from both ears, leading to better speech perception. Given that there are binaural advantages from using cochlear implants with hearing aids in opposite ears, clinicians should advise parents and other professionals about these potential advantages, and facilitate bilateral amplification by adjusting h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
166
3
6

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(191 citation statements)
references
References 20 publications
16
166
3
6
Order By: Relevance
“…This result is contrary to the findings of Gifford and colleagues [27], who reported that the CNC word recognition scores of a group of 36 adults using BMS (M = 71.8% correct) were significantly higher than those of a group of 162 adult using a unilateral CI (M = 55.7%). They are also not in agreement with the general consensus of within-group comparison studies, which indicate that CI recipients with residual hearing in their non-implanted ear obtain higher word recognition scores using BMS than when only using their CI [8,24,34]. However, upon further examination we found that the proportion of users in the BMS group (80%) who obtained scores of ≥ 80% correct was significantly larger than the proportion of CI-only (25%; p = 0.038) and HA-only users (16.7%; p = 0.022) who did the same.…”
Section: Speech Recognitioncontrasting
confidence: 86%
See 2 more Smart Citations
“…This result is contrary to the findings of Gifford and colleagues [27], who reported that the CNC word recognition scores of a group of 36 adults using BMS (M = 71.8% correct) were significantly higher than those of a group of 162 adult using a unilateral CI (M = 55.7%). They are also not in agreement with the general consensus of within-group comparison studies, which indicate that CI recipients with residual hearing in their non-implanted ear obtain higher word recognition scores using BMS than when only using their CI [8,24,34]. However, upon further examination we found that the proportion of users in the BMS group (80%) who obtained scores of ≥ 80% correct was significantly larger than the proportion of CI-only (25%; p = 0.038) and HA-only users (16.7%; p = 0.022) who did the same.…”
Section: Speech Recognitioncontrasting
confidence: 86%
“…This may be due to a better perception of lower frequency phonemes with more information provided regarding the place and manner of articulation compared with a CI-alone [8].…”
Section: Speech Recognitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some additional advantages of the combined mode were also reported; however, they were related to overcoming head shadow effects when listening through two ears. The acoustic ear was found to also contribute to speech recognition in quiet by providing some low-frequency speech information in Ching et al (2001); the low-frequency acoustic hearing provided increased perception of voicing and manner, which, as discussed previously, are dependent upon low-and mid-frequency cues. Gifford et al (2007) reported similar advantages in speech recognition from acoustic hearing contralateral to the implanted ear.…”
Section: Hearing Aids In the Contralateral Earsupporting
confidence: 52%
“…There is evidence to suggest that HAs in the non-implanted ear can offer benefits on measures of speech understanding in noise in adult listeners (e.g., Armstrong et al, 1997;Ching et al, 2001Ching et al, , 2004Tyler et al, 2002;Kong et al, 2005) and location acuity (Ching et al, 2001;Tyler et al, 2002). Similarly, in some children benefits have been seen on tasks involving sound location identification and speech understanding in noise, although the effect sizes are very small (e.g., Ching et al, 2001). Kong et al (2005) have suggested that HAs can lead to improvements whereby fine structure acoustic information at low frequencies is combined with highfrequency envelope information, compensating for limitations in the CI signal processing and electrode design.…”
mentioning
confidence: 99%